SOD1 oxidation and formation of soluble aggregates in yeast: Relevance to sporadic ALS development - Dorival Martins; Ann M. English (Redox Biology, 2014)
Misfolding and aggregation of copper–zinc superoxide dismutase (Sod1) are observed in neurodegenerative diseases such as amyotrophic lateral sclerosis (ALS). Mutations in Sod1 lead to familial ALS (FALS), which is a late-onset disease. Since oxidative damage to proteins increases with age, it had been proposed that oxidation of Sod1 mutants may trigger their misfolding and aggregation in FALS. However, over 90% of ALS cases are sporadic (SALS) with no obvious genetic component. We hypothesized that oxidation could also trigger the misfolding and aggregation of wild-type Sod1 and sought to confirm this in a cellular environment. Using quiescent, stationary-phase yeast cells as a model for non-dividing motor neurons, we probed for post-translational modification (PTM) and aggregation of wild-type Sod1 extracted from these cells. By size-exclusion chromatography (SEC), we isolated two populations of Sod1 from yeast: a low-molecular weight (LMW) fraction that is catalytically active and a catalytically inactive, high-molecular weight (HMW) fraction. High-resolution mass spectrometric analysis revealed that LMW Sod1 displays no PTMs but HMW Sod1 is oxidized at Cys146 and His71, two critical residues for the stability and folding of the enzyme. HMW Sod1 is also oxidized at His120, a copper ligand, which will promote loss of this catalytic metal cofactor essential for SOD activity. Monitoring the fluorescence of a Sod1-green-fluorescent-protein fusion (Sod1-GFP) extracted from yeast chromosomally expressing this fusion, we find that HMW Sod1-GFP levels increase up to 40-fold in old cells. Thus, we speculate that increased misfolding and inclusion into soluble aggregates is a consequence of elevated oxidative modifications of wild-type Sod1 as cells age. Our observations argue that oxidative damage to wild-type Sod1 initiates the protein misfolding mechanisms that give rise to SALS.